2018
DOI: 10.1039/c7ta08780b
|View full text |Cite
|
Sign up to set email alerts
|

Bulk properties and transport mechanisms of a solid state antiperovskite Li-ion conductor Li3OCl: insights from first principles calculations

Abstract: Systematic study on bulk properties, defect chemistry and Li-ion transport mechanisms of a Li3OCl fast-ion conductor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 36 publications
10
61
0
1
Order By: Relevance
“…Timeline of SSEs and electrode/SSEs interface design strategies. [37,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] From 2011 to 2020, the contents of this figure are classified and summarized into cathode/SSE interface, SSEs, and anode/SSE interface based on the statistical results of Web of Science. Reproduced with permission.…”
Section: Introductionmentioning
confidence: 99%
“…Timeline of SSEs and electrode/SSEs interface design strategies. [37,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] From 2011 to 2020, the contents of this figure are classified and summarized into cathode/SSE interface, SSEs, and anode/SSE interface based on the statistical results of Web of Science. Reproduced with permission.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Although the high Li-ion conductivities of Li-rich antiperovskite materials have been known for decades, 12,13 it is only recently that significant interest has been generated for solid electrolyte applications. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Zhao and Daemen 14 reported high ionic conductivities (410 À3 S cm À1 at room temperature) and low activation energies (0.18-0.26 eV) for Li 3 OX-based compositions, where X = Cl or Br. However, subsequent reports have noted reduced Li-ion conductivities and increased activation barriers for these materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent reports have noted reduced Li-ion conductivities and increased activation barriers for these materials. [16][17][18][19][20][21]23 It has been suggested that the as-prepared samples in the work of Zhao and Daemen were in fact hydrated compositions, i.e., Li 2 OHCl, 19 based on their hygroscopic nature. 12,13,15,19,22 The measured ionic conductivities of these materials are known to be highly dependent on the sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, the extrema of the conduction band and the valence band are located at the Ŵ and Z point in the first Brillouin zone, respectively, which thus leads to a large indirect band gap of 3.77 eV. This indicates that the Li 2 GeO 3 compound has an excellent electrochemical stability and provides a negligible electronic conductivity (Wu et al, 2018). However, the investigations for the band structure of the Li 2 GeO 3 compound are rather limit up to now; therefore, the present results may provide a helpful information for the future work.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…On the theoretical side, a number of studies using the molecular dynamics (MD) and density functional theory (DFT) were investigated on the phase stability (Emly et al, 2013;Zhang et al, 2013;Kaboudvand et al, 2019), defect structure (Lu et al, 2015;Kuganathan et al, 2019), electronic properties (Kaboudvand et al, 2019) and the Li + transport mechanisms (Emly et al, 2013;Lu et al, 2015;Wu et al, 2018;Kuganathan et al, 2019) of the electrodes or electrolyte materials of LIBs. The complicated atomic interactions (multi-orbital hybridizations) are generated from the diversified physical or chemical properties and the complex material structure.…”
Section: Introductionmentioning
confidence: 99%